UJI AKTIVITAS KLOROFIL BEBERAPA JENIS SAYURAN SEBAGAI ANTIBAKTERI TERHADAP Escherichia coli DAN Staphylococcus aureus - Munira Munira; Novi Yanti; Muhammad Nasir (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2021)
Background: Chlorophyll is a green color pigment in plants, algae and photosynthetic bacteria. The chlorophyll contained in the leaves has a function as an antioxidant, anti-inflammatory, and antibacterial. This study aims to determine the ability of chlorophyll from several types of vegetables to inhibit Escherichia coli and Staphylococcus aureus and determine the differences in the diameter of the inhibition zone between them. Methods: This study was a laboratory experimental study using a completely randomized design (CRD) divided into 4 treatments, namely aquadest (P0), cassava leaf chlorophyll (P1), kale leaf chlorophyll (P2), and spinach leaf chlorophyll (P3). 6 repetitions each. Microbiological tests were carried out using the well diffusion method. Results: Anova test showed that the chlorophyll extracts of cassava, kale and spinach were very influential (P = 0.000) in inhibiting the growth of Escherichia coli and Staphylococcus aureus. Duncan's further test showed that the largest average inhibition zone diameter for Escherichia coli was formed by cassava leaf chlorophyll (17.66 mm) and was significantly different from kale leaf chlorophyll (7 mm) and spinach leaves (6.16 mm). Similar to Staphylococcus aureus, the largest average inhibition zone diameter was also formed by cassava leaf chlorophyll, which was 18.16 mm and significantly different from kale leaf chlorophyll (6.75 mm) and spinach leaves (6.08 mm). Conclusion: The chlorophyll extract of cassava leaves, kale and spinach can inhibit the growth of Escherichia coli and Staphylococcus aureus with the largest inhibition zone diameter formed by the chlorophyll extract of cassava leaves.